EFEKTIVITAS PENGOLESAN TAF (TOPICAL APPLICATION FLUORIDE) TERHADAP PENCEGAHAN KARIES PADA ANAK USIA 2-9 TAHUN DI RSGM UMY - Ayu Nurdiandari (FKG 14 UMY 427, 2014)
TAF (Topical Application Fluoride) is one of the most efective way to prevent the caries. It can also prevent the caries and makes stronger the teeth to reduce the subtitution eruption, to produce the calcium, to smooth the surface and dentin. The study is to know the efectivity of TAF (Topical Application Fluoride) to prevent the caries in children 2-9 years old at RSGM UMY. The study is observational in cross sectional with the qualitative and quantitative approach. The study was done at RSGM UMY AMC (Asri Medical Center) in May to June 2014. The subject is medical record of 48 children in 2 to 9 years old who have deciduous and permanent teeth care in mix teeth period at RSGM UMY who have inclusion criteria. Number of children 2 to 9 years old on TAF (Topical Application Fluoride) is 48 children (100%) who have effectivity. TAF (Topical Application Fluoride) on children 2 to 9 years old at RSGM UMY is effective to prevent the caries.